Evaluación por competencias en la comprensión de textos escritos en inglés en estudiantes de quinto grado de secundaria en instituciones educativas públicas del distrito de Iquitos 2023 - Cuipal Mendoza, Julio Angel (2024)
The purpose of the present research study was to explain the influence of competency-based assessment in the fifth grade on secondary public schools’ students English reading skills in the district of Iquitos 2023. The research type was explanatory with field study, contemporary transectional, and multivariate designs. The population was made up of 2463 students, with a proportional allocation in stratified sampling of 332. The results for the competency-based assessment variable show that the mean score was 83,740 on a scale transformed to 100. Regarding the English reading skill variable, the mean score was 5,275 out of 20 (vigesimal scale), which indicates that students are at a pre beginning level of achievement, while the mean score in its dimensions was: getting information (6,822), inference and interpretation of information (3,477), and form, content, and context evaluation (5,539). The correlation index of the study variables was r = 0,104, with a p-value of 0,464 > α = 0.05. In conclusion, as the correlation was inexistent between the study variables, there was no need to analyze the regression; therefore, there is no influence of competency-based assessment on English reading skill in the study population, rejecting the working hypothesis.